(untitled) (American Journal of Islam and Society, 2013)
The recent political upheavals in the Arab world were marked by women’s significant presence in struggling for democracy alongside men. Muslim women activists in Morocco have particularly gained legitimacy in the context of the Arab Spring, which has brought the Justice and Development conservative political party to power. This has contributed to a shift from the elite liberal state feminism to a more legitimate religious activism. This introduces new spaces for contention, taking into consideration that following the 2003 Casablanca bombings, Morocco has taken a series of measures to absorb the growing momentum of political Islam. One such measure has been to restructure the religious field by means of reforming and controlling the dynamics of religion in Morocco; this was primarily marked by the significant entry and deployment of women in the religious field as religious leaders and scholars. These statetrained female religious authorities offer spiritual counseling and religious instruction to different social segments. Therefore, they redefine parameters of religious authority and define a new model of activism that seeks to cultivate collective pious conduct within society and thus contribute to a comprehensive social reform. Therefore, this article explores the dynamics of female religious authority in Morocco in light of the current social and political changes. I examine how these women construct authority as religious leaders and how they endorse the state’s authority to control the dynamics of religion in Morocco and curb the voices of individuals or groups that operate outside of official Islam. I argue that despite the fact that these female religious authorities are viewed as instruments of state propaganda, they are gaining wider legitimacy and contributing greatly to the social welfare of their communities, which makes their “official” entry into the religious domain a serious step toward democracy and positive change.